Low-cost animal drawn implements for Vertisol management and strategies for land use intensification - Astatke, A.; Jabbar, M.A. (CAB International, 2001)
This paper discusses the traditional management of vertisols and land-use types the broadbed maker (BBM) and its evolution; Maresha - a traditional plough; additional attachements to the BBM for improving tillage efficiency and resource conservation; the land-use intensification opportunities; and research needs and opportunities